RASIO KEUANGAN MODEL ALTMAN Z”-SCORE PENGARUHNYA TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022 - VICTORIA, NAEMA; FRIYANTO; HARITSAR, YOSAR (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
The purpose of this study was to determine and analyze the ratio of Working Capital to Total Asset (WCTA), Retained Earnings to Total Asset (RETA), Earning Before Interest and Taxes to Total Asset (EBITTA), and Book Value of Equity to Book Value of Total Debt (BVEBVTD) partially and simultaneously affect Financial Distress in telecommunication sub-sector companies listed on the IDX 2018-2022 period. This study uses descriptive quantitative methods using secondary data from financial statements for five years. The population of this study were all telecommunications sub-sector companies in Indonesia as many as 21 companies with sample withdrawal using purposive sampling method and 16 companies were taken during 2018-2022. The data analysis method used in this research is multiple linear regression analysis using the help of Ms. Excel and SPSS software version 26. The results showed that (1) WCTA has a partial effect on Financial Distress with the results of a significant partial effect (t test) (p=0.000 <0.05). (2) RETA has a partial effect on Financial Distress with significant partial effect results (t test) (p=0.000 <0.05). (3) EBITTA has a partial effect on Financial Distress with the results of a significant partial effect (t test) (p=0.025 <0.05). (4) BVEBVTD has no effect on Financial Distress with the results of a significant partial effect (t test) (p=0.891> 0.05). (5) Simultaneously, WCTA, RETA, EBITTA, BVEBVTD simultaneously affect Financial Distress with the results of simultaneous influence (F test) significant (p=0.000 <0.05).